Development of the stock market in Kazakhstan - Imangali, Unzila (2025)
This thesis examines the evolution, current state, and future prospects of the stock market in the Republic of Kazakhstan. It begins by exploring the theoretical foundations of stock market functions and efficiency, followed by an in-depth historical and institutional analysis of Kazakhstan’s capital markets, with a particular focus on the Kazakhstan Stock Exchange (KASE) and Astana International Exchange (AIX). The research presents a comparative study between Kazakhstan’s stock market and those of other emerging economies, highlighting structural differences and convergence trends. An empirical assessment using weak-form Efficient Market Hypothesis (EMH) tests is conducted for the 2014–2024 period, revealing partial market efficiency with anomalies and investor behavior that deviate from classical theory. Finally, the thesis outlines strategic development scenarios for the Kazakh stock market through 2030, proposing policy recommendations aimed at enhancing liquidity, market depth, and integration with international financial systems.